"This is us": Free speech embedded in whiteness, racism and coloniality in Aotearoa, New Zealand. Issue 2 (2nd July 2020) - Elers, Christine Helen; Jayan, Pooja
ABSTRACT: Whiteness as an ideology is the default norm constituting the infrastructures of New Zealand's polity. Built with the master's tool of racism, the mechanics of free speech in Aotearoa, New Zealand is embedded in whiteness that holds fast to liberal expressions of free speech, while dehumanising and denigrating indigenous and minority coloured realities. New Zealand's ambivalence towards legislative acknowledgement that Māori tribal nations did not cede sovereignty to a foreign land as confirmed in te- Tiriti o Waitangi, is an epic human rights violation that is the precursor to a litany of human rights violations upon Māori and minority groups that followed. Freedom of speech discourse has been utilised as an impenetrable shield to justify threatening, offensive and abusive attacks – both psychologically and physically upon indigenous and minority groups. Massey University's pursuit of a te-Tiriti led university actioned the cancelling of a known public speaker that negatively targets and stereotypes Māori, leading to national outrage at the perceived denial of the right to freedom of speech. The effects of racist and dehumanising speech upon targeted groups was again missing from public discourse. We attempt to illuminate the marginalised realities of indigenous and minority groups on the flipside of free speech discourse.